The Effect of Environmental, Social, and Governance (ESG) Performance on Firm Value: A Comparative Study Between State-Owned and Non-State-Owned Enterprises (An Empirical Study of Companies Listed on the Indonesia Stock Exchange for the 2020–2023 Period) - Ni Putu Alit Febrianti; I Ketut Suryanawa; Ni Putu Sri Harta Mimba; Ni Made Dwi Ratnadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Firm value represents the long-term goal of a company, reflecting the prosperity of its stakeholders. One factor indicated to influence firm value is corporate responsibility performance in managing business operational risks, particularly through the implementation and disclosure of Environmental, Social, and Governance (ESG) performance. During the COVID-19 pandemic, the Indonesian government allocated State Capital Participation (PMN) to affected state-owned enterprises (SOEs), which was expected to contribute to the revitalization of national economic recovery. This study aims to analyze the effect of ESG performance on firm value in both SOEs and non-SOEs listed on the Indonesia Stock Exchange during the 2020–2023 period. Stakeholder theory and signaling theory are used as the theoretical frameworks for analyzing and interpreting the research findings. The sample consisted of 28 observations for SOEs and 152 for non-SOEs, selected using purposive sampling. Firm value was measured using the Tobin’s Q ratio, while ESG performance was assessed based on Refinitiv scores. The data were analyzed using independent sample t-tests and multiple linear regression analysis with SPSS version 29. The results show significant mean differences in environmental and social performance between SOEs and non-SOEs, while governance performance did not differ significantly. Social and governance performance had a significant positive effect on firm value in both SOEs and non-SOEs. However, environmental performance had a significantly positive effect only in non-SOEs and a significantly negative effect in SOEs. Thus, the environmental performance strategies implemented by non-SOEs could serve as valuable lessons for SOEs.